2022
DOI: 10.1186/s12935-022-02535-9
|View full text |Cite
|
Sign up to set email alerts
|

DAB2IP predicts treatment response and prognosis of ESCC patients and modulates its radiosensitivity through enhancing IR-induced activation of the ASK1-JNK pathway

Abstract: Background Disabled homolog 2 interacting protein (DAB2IP) plays a tumor-suppressive role in several types of human cancers. However, the molecular status and function of the DAB2IP gene in esophageal squamous cell carcinoma (ESCC) patients who received definitive chemoradiotherapy is rarely reported. Methods We examined the expression dynamics of DAB2IP by immunohistochemistry (IHC) in 140 ESCC patients treated with definitive chemoradiotherapy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In esophageal squamous cell carcinoma (ESCC) cells, expression of DAB2IP was shown to reduce resistance to ionizing radiation; in vitro, DAB2IP overexpressing cells displayed higher apoptosis after cisplatin treatment and IR exposure. In nude mice, DAB2IP expression did not affect the growth rate of ESCC xenografts, but after IR treatment DAB2IP-expressing tumors were significantly reduced compared to controls [44].…”
Section: Dab2ip Loss Promotes Resistance To Chemo-and Radio-therapiesmentioning
confidence: 78%
See 1 more Smart Citation
“…In esophageal squamous cell carcinoma (ESCC) cells, expression of DAB2IP was shown to reduce resistance to ionizing radiation; in vitro, DAB2IP overexpressing cells displayed higher apoptosis after cisplatin treatment and IR exposure. In nude mice, DAB2IP expression did not affect the growth rate of ESCC xenografts, but after IR treatment DAB2IP-expressing tumors were significantly reduced compared to controls [44].…”
Section: Dab2ip Loss Promotes Resistance To Chemo-and Radio-therapiesmentioning
confidence: 78%
“…Enhanced IR-induced activation of the ASK1/JNK pathway Increased apoptosis after cisplatin treatment and ionizing radiation (IR) in vitro; reduced tumor size after IR in vivo [44] Colorectal cancer Inhibition of AKT and ERK activation; regulation of HSP90AA1/SRP9/ASK1/JNK signaling axis Decreased cell growth and migration in vivo and increased sensitivity to chemotherapeutic drugs in vitro [42] Inducing c-Myc degradation via GSK3βmediated phosphorylation…”
Section: Dab2ip Loss Supports a Pro-metastatic Tumor Microenvironmentmentioning
confidence: 99%
“…In our study, it presented a higher level in high-risk BC patients, which also hinted at the inferior outcome in this group and was listed as a potential target for BC treatment. DAB2IP belonged to the Ras GTPase-activating protein family and played an anti-tumor role in multiple cancers, such as esophageal squamous cell carcinoma ( 48 ), and triple-negative breast cancer ( 49 ). Additionally, in TBNC, it was shown that the expression of DABI2P was able to alleviate chemoresistance ( 49 ), which means that it was a promising market to improve the prognosis of BC patients.…”
Section: Discussionmentioning
confidence: 99%
“…DAB2IP was first reported as a DOC-2/DAB2 interacting protein and has been shown to suppress cell proliferation and metastasis. 18 , 19 , 20 , 21 As a scaffold protein, DAB2IP comprises multiple domains involved in various pro-oncogenic signaling pathways, including β-catenin/TCF, 22 NF-κB signaling, 23 ASK1/JNK, 44 and PI3K/AKT. 45 Considering that the DAB2IP protein itself has no kinase function, we screened for potential tyrosine kinases using a RTK phosphorylation antibody microarray.…”
Section: Discussionmentioning
confidence: 99%